La codificación de la noción ‘verdadero’ en la gramática - Kornfeld, Laura Malena (2025)
In this paper, we aim to discuss the processes of grammaticalization involving the notion of ‘verdadero’ across different categorial domains, based on the analysis of three phenomena from different varieties of colloquial Spanish: lexical reduplication, registered in general Spanish (Escandell Vidal 1991, Roca y Suñer 2000, Feliú 2011); the expression posta in Rioplatense Spanish; and the loan of the suffix ité in Spanish in contact with Guarani (Abadía de Quant 1996, Avellana y Kornfeld 2009, Kornfeld 2012). This will allow us not only to contribute to the grammatical description of these specific varieties, but also to make a genuine contribution to the study of grammaticalization and the search for universal patterns in Heine y Kuteva (2002).